Electric Vehicle Policy: The Main Pillar of Indonesia's Future Energy Security - I Made Suraharta; Nico Djundharto Djajasinga; Muhammad Bagus Adi Wicaksono; Ryan Aldiansyah Akbar; Noviaji Joko Priono; Mochamad Aris Yusuf; Rudy Max Damara Gugat (International Journal of Science and Society, 2022)
Indonesia still has a high dependence on fossil energy. This can be seen through how the use of fossil energy still dominates the energy needs in Indonesia. Most of this fossil energy comes from oil sources. However, the increasing use of energy and the reduction in fossil energy reserves has made Indonesia need to use renewable energy. This needs to be done to achieve energy security in Indonesia. This research will be carried out to see how the conceptual framework and policies regarding energy security in transportation in Indonesia through electrical energy can support energy security in Indonesia. This research will be carried out using a literature study approach. According to the findings of this study, there are multiple concepts in energy security, including the availability of existing energy resources that can meet energy demand, existing support in facilities such as distribution, transportation, and production division that can meet energy consumption needs, and the minimal negative impact of energy production and consumption on human health and the surrounding environment.